1971
DOI: 10.1115/1.3449790
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Solution for Natural Convection in Cylindrical Annuli

Abstract: The results of a finite-difference solution for natural convection within horizontal cylindrical annuli for Prandtl numbers near 0.7 (air) are presented.The ranges of Rayleigh number and inverse relative gap width over which such a solution yields valid results are investigated.It is shown that this solution, though formulated for steady flow, can be used to obtain an indication of the Rayleigh number at which transition from ft steady to an unsteady flow will occur for a wide range of inverse relative gap wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

1976
1976
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(30 citation statements)
references
References 8 publications
(22 reference statements)
2
27
0
1
Order By: Relevance
“…For other than very small Prandtl numbers, only a few numerical studies of posttransitional flow in a horizontal annulus have been published. In nearly all of these studies, a two-dimensional model was employed (Powe, Carley & Carruth 1971 ;Fant, Rothmayer & Prusa 1991 ;Cheddadi et al 1992 ;Yoo 1996) and therefore neither the spiral secondary flows which are observed experimentally in annuli of moderate R nor the influence of solid endwalls which bound a finite-length annulus could be analysed. Rao et al (1985) carried out steady three-dimensional calculations for a case of moderate R. However, only a fluid with Prandtl number of 5000 was studied which limits the range of practical applicability of their results.…”
Section: Introductionmentioning
confidence: 99%
“…For other than very small Prandtl numbers, only a few numerical studies of posttransitional flow in a horizontal annulus have been published. In nearly all of these studies, a two-dimensional model was employed (Powe, Carley & Carruth 1971 ;Fant, Rothmayer & Prusa 1991 ;Cheddadi et al 1992 ;Yoo 1996) and therefore neither the spiral secondary flows which are observed experimentally in annuli of moderate R nor the influence of solid endwalls which bound a finite-length annulus could be analysed. Rao et al (1985) carried out steady three-dimensional calculations for a case of moderate R. However, only a fluid with Prandtl number of 5000 was studied which limits the range of practical applicability of their results.…”
Section: Introductionmentioning
confidence: 99%
“…From numerical results obtained in this study, and results discussed in Powe et (1971) and Rao et (1985), it can be seen that the narrow-gap solutions for flows prior to multicellular transition (and even beyond to a certain extent) behave in a seemingly steady-state manner. Assuming the steady-state condition and using the leading-order solution of Eq.…”
Section: The Perturbât!ve Solution To the Steady-state Finite-prandtlsupporting
confidence: 57%
“…Therefore, the multicellular regime that is associated with the narrow type gaps (at high Rayleigh number) most likely reverts back to two cells and then, finally to a pure conductive mode when the velocities tend to zero as G -»• 0 (or G + 0 for a specified Rayleigh number). Contrary to this result, many investigators (Walton, 1980;Powe et , 1971;Liu et£!_., 1962) believed that as the gap approached zero, a true Bénard type instability would evolve, where the typical critical Rayleigh number (Ray_a) of about 1,700 is approached. Instead, it appears that after a certain point, the transitional Rayleigh number increases with decreasing gap size (to well above 1,700), until eventually, a conductiondominated flow results as the gap approaches zero (see Chapter 6).…”
Section: The Boundary-layer Expansionmentioning
confidence: 93%
“…There are several researches on both numerical and experimental investigation of natural convection heat transfer between two concentric circular cylinders. Powe et al (1971) studied numerical solution for natural convection in cylindrical annuli and classified the flow patterns conferring to suitable combinations of the Rayleigh number and the radius ratio. Kuehn and Goldstein (1976) conducted an experimental and theoretical study of natural convection in an annulus between horizontal concentric cylinders.…”
Section: Introductionmentioning
confidence: 99%